PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INVESTIGASI KELOMPOK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMAN BUKITTINGGI - Majidah Khairani (STKIP Pesisir Selatan, 2016)
This study aims to mathematical problem solving ability of students after being given treatment model of cooperative learning investigative research design used in this study is a quasi-experimental research and shaped